2015
DOI: 10.1517/14728222.2015.1071355
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference for multiple myeloma therapy: targeting signal transduction pathways

Abstract: Recent advances in oncogenomic studies have revealed the molecular pathogenesis of MM, thus providing new therapeutic targets for RNAi therapy. Pre-clinical evidence suggests that non-viral delivery technology offers the potential to translate this concept into the next generation of RNAi-based therapeutics for MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 100 publications
(142 reference statements)
1
8
0
Order By: Relevance
“…The results of this previous study indicated that LNA-i-miR-221 harbored a short half-life, optimal tissue bioavailability and minimal urine excretion in mice and monkeys and revealed no toxicity in the pilot monkey study. Therefore, miRNA-based therapy is a promising novel therapeutic method for MM ( 100 , 101 ).…”
Section: Mirna-based Therapeutic Strategies In MMmentioning
confidence: 99%
“…The results of this previous study indicated that LNA-i-miR-221 harbored a short half-life, optimal tissue bioavailability and minimal urine excretion in mice and monkeys and revealed no toxicity in the pilot monkey study. Therefore, miRNA-based therapy is a promising novel therapeutic method for MM ( 100 , 101 ).…”
Section: Mirna-based Therapeutic Strategies In MMmentioning
confidence: 99%
“…Different signal pathways are involved in the development and drug-resistance of MM, including PI3K/AKT/mTOR, RAS/RAF/MEK/ERK, JAK/STAT, WNT/β-catenin and NF-κB [25]. The binding of MM cells to BM stromal cells triggers adhesion- and cytokine-mediated MM cell growth, survival and migration through activation of p42/p44 MAPK [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, M protein classification cannot cover all patients with MM and this disease has been found to have a great heterogeneity at the genetic level. Therefore, researchers have focused on the field of genetic molecular research as regards MM in the hope of identifying novel individualized biomarkers and treatment for this disease (4,5).…”
Section: Introductionmentioning
confidence: 99%